Analysis of New Energy Vehicle Marketing Strategy - Taking Xiaomi as an Example - Zheng Xiangyu (SHS Web of Conferences)
The global automotive industry is accelerating its transformation to new energy vehicles, affected by climate change, energy crisis, and policy promotion. As a leading technology company in China, Xiaomi announced its entry into the new energy vehicle industry in 2021 and launched its first smart electric car Xiaomi SU7 at the end of 2023. This study analyzes the marketing strategy of Xiaomi’s new energy vehicles and explores its advantages and challenges in a highly competitive market environment. This paper adopts case analysis, data comparison, and policy analysis methods to discuss market segmentation, product differentiation, and channel expansion. The results show that Xiaomi has successfully shaped a differentiated competitive advantage by relying on its smart ecosystem, smart driving technology, and cost-effective strategy. At the same time, the combination of online direct sales and offline experience stores has increased market penetration. However, Xiaomi still faces challenges in brand awareness, supply chain management, and after-sales service. This study believes that Xiaomi should deepen the integration of smart ecology, optimize the supply chain, and increase investment in autonomous driving technology to enhance its market competitiveness.